Ecological study on Uyun Layla in Saudi Arabia - Wafaa Mohammed Al-Ghanem (African Journal of Environmental Economics and Management, 2019)
Soil characters and vegetation types have been investigated in the desiccated Uyun Layla lakes from October, 2007 till May, 2010, except during the summer months. The vegetation in and between the 23 dolines was very poor. Twenty xerophytic species were recorded mainly Zygophyllum coccineum, Zygophyllum simplex, Salsola spp., Traganum nudatum, Haloxylon salicornicum, Zilla spinosa, Rhanterium epapposum and Gymnocarpos decandrum. The importance value (I.V.) of all the species has been calculated and their taxonomic position has been described. The soil was sandy, yellowish white and very poor in minerals. In spite of that, the total soluble salts, calcium and copper contents were considerably high. The results have been discussed and interpreted according to the environmental changes occured in this area.